Evidence for a Single Large Igneous Province at 2.11 Ga across Supercraton Superia. (22nd April 2022) - Davey, Sarah C; Bleeker, Wouter; Kamo, Sandra L; Ernst, Richard E; Cousens, Brian L; Vuollo, Jouni; Huhma, Hannu
Abstract: The Superia supercraton palaeogeographic reconstruction (c. 2.65–2.00 Ga) is predominantly based on the shared large igneous province (LIP) record of the Superior, Hearne, Wyoming, and Karelia-Kola Archaean cratons. Palaeogeographic reconstruction relies on U–Pb geochronology (i.e. magmatic barcodes), palaeolatitudes from palaeomagnetic studies, and geometry of mafic dyke swarms as part of LIPs, as well as similarities in cover stratigraphy and/or basement geology. If contemporaneous mafic units from these cratons are indeed fragments of the same LIP, then integration of their chemistry can provide insight into the overall LIP plumbing system. A geochemical evaluation of whole-rock major and trace elements, and Nd isotopes, is presented for c. 2.11 Ga mafic units from the Marathon dykes (Superior), Griffin gabbro sills and Kazan dykes (Hearne), Bear Mountain dykes (Wyoming), and Tohmajärvi-Pirtguba dykes, Misi gabbro sills, and Oravaara and Hirsimaa volcanic rocks (Karelia-Kola). These units include the Nieminen dyke, Western Karelia, for which we present a new U–Pb CA-ID-TIMS date of 2114.4 ± 3.0 Ma. Four geochemical groups are identified: Groups 1 (mid-ocean ridge basalt-like; in Karelia) and 2 (within plate basalt; in Hearne, Wyoming, and Karelia) are distinct end-members of upper mantle and plume melts, respectively; Group 3 (in Superior, Wyoming, and Karelia) is a hybrid of Groups 1 and 2; and Group 4 (in all cratons) formed by assimilation and fractional crystallisation of Groups 1, 2, and 3. We present a model of the LIP plumbing system and define three magmatic stages by combining our geochemical interpretations with existing geochronology. The early stage (2135–2130 Ma) is limited to Group 1 dykes. The middle stage (2130–2113 Ma) includes Groups 1, 3, and 4. Onset of the late stage (2113–2101 Ma) is marked by the introduction of Group 2 but Groups 1 and 4 are also abundant. Finally, with our integrated tectonic and geochemical model, we discuss the mineralisation potential and prospectivity of the entire c. 2.11 Ga magmatic system.